2005
DOI: 10.1007/s00418-005-0078-9
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical characterisation of sensory receptors in airway smooth muscle: comparison with pulmonary neuroepithelial bodies

Abstract: Descriptions of morphologically well-defined sensory airway receptors are sparse, in contrast to the multiplicity of airway receptors that have been identified electrophysiologically. The present study aimed at further determining the location, morphology and neurochemical coding of subepithelial receptor-like structures that have been sporadically reported in the wall of large diameter airways. The results were compared with those obtained for pulmonary neuroepithelial bodies (NEBs), which are complex intraep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 39 publications
1
38
1
Order By: Relevance
“…-ATPase a3) were used. These markers have been shown to label SMARs in rat airways (Brouns et al 2006b), and vagal (mechano)sensory nerve fibres associated with mouse and rat NEBs (Brouns et al 2006a(Brouns et al , 2009a, and in the present study additionally revealed subepithelial nerve terminals in mouse airways. To check the specific location of subepithelial nerve terminals visualised with VGLUT1, P2X 3 , Na ?…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…-ATPase a3) were used. These markers have been shown to label SMARs in rat airways (Brouns et al 2006b), and vagal (mechano)sensory nerve fibres associated with mouse and rat NEBs (Brouns et al 2006a(Brouns et al , 2009a, and in the present study additionally revealed subepithelial nerve terminals in mouse airways. To check the specific location of subepithelial nerve terminals visualised with VGLUT1, P2X 3 , Na ?…”
Section: Discussionsupporting
confidence: 54%
“…Using immunostaining for the above-mentioned molecules resulted in the identification of SMARs a few years ago. Morphologically, SMARs appear as branching laminar subepithelial receptor-like nerve endings that were found to intercalate in the smooth muscle layer of intrapulmonary conducting airways (Brouns et al 2006b;De Proost et al 2007). In rats, nerve fibres giving rise to SMARs were shown to be myelinated and to have a vagal origin (Brouns et al 2006b).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Since the expression of VGLUTs should be regarded as determining for the capacity of nerve endings to store and release glutamate as a neurotransmitter (Takamori et al 2000), depolarisation of SMAR terminals will likely cause the release of glutamate. Glutamate may consequently serve a local peripheral eVector function (Raab and Neuhuber 2003;Bewick et al 2005), for example inXuencing the activity of neighbouring smooth muscle cells, or may regulate the excitability and/or transduction of the sensory nerve Wbres (Brouns et al 2004(Brouns et al , 2006b.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, prominent discoveries of immunochemically distinct receptor end organs, such as the unmistakable guinea pig cough receptor (10) and the murine smooth muscle-associated airway receptor and neuroepithelial body (NEB) innervation (11), have been conspicuously absent in descriptions of human airway innervation to date (12). The sparsity of such vagal afferent mechanoreceptors in comparison with the easily identified vagal and spinal C fiber counterparts and lack of appropriate antibodies might explain this phenomenon.…”
mentioning
confidence: 99%